A probe with aggregation induced emission characteristics for screening of iodide1. Issue 37 (7th October 2015) - Chopra, Rakesh; Kaur, Paramjit; Singh, Kamaljit
<x xml:space="preserve">Abstract</x> Emission of spherically aggregated form of a triazole based probe dies down upon detecting iodide.